First report on identification and genetic characterization of Getah virus in wild boar in China - Huang, Jian; Song, Deping; Wei, Jiazhen; Xie, Baobao; Yang, Qun; Xu, Jun; Zhang, Fanfan (Frontiers in Microbiology, 2025)
Getah virus (GETV) is a mosquito-borne Alphavirus that causes fever, rash and oedema in horses, fever, anorexia and neurological symptoms as well as piglet diarrhea deaths and reproductive disorders in sows in blue foxes, and the endemic areas are expanding progressively, especially in Asia and Oceania. In order to study the current epidemiological status of GETV in wild boar herds and its genetic and evolutionary patterns, we conducted a survey and genomic analyses of GETV in pig herds. The results showed that 74.02% (57/77) of the samples tested (n = 77) were positive for GETV, with the highest positivity rate of 100% in visceral tissue samples from diarrheic piglets and aborted fetuses, and also for the first time, the presence of GETV was detected in milk and semen. The complete genome of the representative GETV strain JX2024 was determined, and genome wide and E2 gene evolution tree results showed that the representative strain belonged to subtype GIII. Multiple comparison analysis showed that the E2 gene of JX2024 differed at the amino acid level by 96.4% to 99.5% compared with the reference GETV strain, and that the mutation of arginine to lysine at position 253 was the key amino acid site for the enhanced virulence of GETV. This analysis bridges the gap between the molecular epidemiological data and the genetic variation of GETV in wild boar and provides a basis for further understanding of the spread of GETV in China.